Pengaruh Dosis Pupuk N,P,K dan Pupuk Hayati Terhadap Pertumbuhan dan Hasil Padi Sawah Varietas INPARI 32 - Firdaus, Imron; Abdullah, Rohana; Taryana, Yana (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
The experiment was carried out in the paddy fields of the Mukti IV farmer group, Ciasem Girang Village, Ciasem District, Subang Regency, with an altitude of 25.11. The aim of the research was to examine and analyze the doses of N,P,K and biological fertilizers for the growth and yield of the Inpari 32 rice variety. And to obtain the optimum doses of N,P,K and biological fertilizers that can have the best effect on growth and yield of lowland rice varieties Inpari 32. The design used was a factorial Randomized Block Design (RBD) consisting of two factors and three repetitions. The first factor is the dose of N,P,K fertilizer (p) which consists of three levels, namely: p1 = without biological fertilizer (100% ha-1), p2 = N,P,K fertilizer (60%), p3 = fertilizer N,P,K (20 %). The second factor is biological fertilizer (h) which consists of 3 levels, namely: h0 = (0 kg ha-1), h1 = (15kg ha-1), h2 = (30 kg ha-1). The experimental results showed that the doses of N, P, K and biological fertilizers affected the growth of plant height (21 DAP), number of tillers (28 DAP), and yield (grain weight per clump).